2000
DOI: 10.1097/00001756-200003200-00012
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for extraocular light induced phase shifting of human melatonin, cortisol and thyrotropin rhythms

Abstract: The view that light affects the mammalian circadian clock only through the eyes was recently challenged by a study in which the phases of human circadian rhythms were shifted by extraocular light exposure. This finding has not been confirmed, however. We studied the effects of light exposure (3 h, broad spectrum fluorescent white light, 13000 lux) on abdomen and chest on the circadian rhythms of serum melatonin, cortisol and thyrotropin in six subjects. The protocol consisted of two 3-day sessions in a dimly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
2
7
1
Order By: Relevance
“…All but two of the subjects (86%) exhibited an increase in REM sleep. This finding is in contrast to several recent studies that have failed to demonstrate an effect of extraocular light administration on other central nervous system activities (10,14,18,25,27,53).…”
Section: Discussioncontrasting
confidence: 99%
“…All but two of the subjects (86%) exhibited an increase in REM sleep. This finding is in contrast to several recent studies that have failed to demonstrate an effect of extraocular light administration on other central nervous system activities (10,14,18,25,27,53).…”
Section: Discussioncontrasting
confidence: 99%
“…The most recent of these was by researchers from Cornell University, who suggested that bright light applied to the area behind the human knee would shift circadian rhythms of body temperature and melatonin (Campbell and Murphy 1998). But like earlier reports, these studies have not withstood independent verification (Koorengevel et al 2001;Lindblom et al 2000aLindblom et al , 2000bLockley et al 1998), suggesting that the original observations resulted from some unrecognised artefact of the experimental procedures (Foster 1998;Yamazaki et al 1999).…”
Section: Light Circadian Rhythms and Novel Ocular Photoreceptorsmentioning
confidence: 96%
“…Nonetheless, some scientists challenged the findings at the time for pragmatic reasons; namely, that eye loss in humans blocks photoentrainment [ 188 ]. Other groups attempted to replicate these findings using various approaches [ 189 , 190 , 191 ] and then the methodologies were replicated precisely [ 192 ]. All failed to show that light applied to the popliteal region would phase shift the circadian system.…”
Section: The Effects Of Light On the Human Circadian Systemmentioning
confidence: 99%